(untitled) (Bangladesh Medical Journal, 2010)
The patients investigated under this study have complaints of inability to conception and they were not responding to treatment. Patients with infertility were studied, the peak incidence of infertility was found in between 26-29 years of age group. Hysterosalpingography examination detected tubal and uterine pathology correctly in 26 cases (81.25%) out of 29 cases of complaining of infertility. Of 18 negative cases, 12 cases (80%) are diagnosed correctly as normal by Hysterosalpingography. After laparoscopic examination it was established that three (20%) were false positive and 6 cases were false negative. If a longer series are analyzed, these findings may vary slightly but still it is very useful diagnostic tool for detection of infertility. Hysterosalpingography will give utmost benefit to the patients of our country. In our study we found that Hysterosalpingography is still the best technique for intrauterine and tubal pathology. This study has established the fact that Hysterosalpingography should be the first approach in the diagnosis of infertility which gives valuable information about both uterine cavity and fallopian tubes at low risk and minimal hazards. As a result of our findings, it is our investigation of female infertility due to its potential accuracy and easy performance Keywords: Hysterosalpingography; Infertility. DOI: 10.3329/bmj.v39i1.6228 Bangladesh Medical Journal 2010; 39(1): 16-23